СOMMUNICATIVE ABILITIES IN THE SCIENCE OF PSYCHOLOGY - Maysarabonu Alimova (Journals Park Publishing, 2022)
The article talks about communicative abilities in psychology and their scientific theoretical study. In order to cover the topic of the article, scientific works of foreign and local scientists were effectively used. The results obtained from the article can be used positively in the study of communicative abilities in the science of psychology.
Keywords: psychology; communicative abilities; theoretical